KEPATUHAN MASYARAKAT PADA PENERAPAN KEBIJAKAN NEW NORMAL DI KECAMATAN TOMOHON BARAT KOTA TOMOHON - Irene Kawatu; Arie Rorong; Very Londa (Sam Ratulangi University, 2023)
Abstract The purpose of this research is to determine the factors that influence people's compliance with the new normal policy in the West Tomohon sub-district. The Indonesian government's new normal policy allows economic and social activities involving health issues. Data collection methods used on 12 informants included interviews and observations. According to the study's findings, knowledge, motivation, and family support are factors influencing public compliance with the new normal policy. The knowledge factor is critical to increasing compliance with the new normal policy. Knowing people, the consequences of breaking the new normal policy will be less severe. Furthermore, motivational factors are known to play an important role because they are the forces that encourage individuals to act and comply with the new normal policies. Family support factors, on the other hand, can provide motivation, confidence, and a good example for other family members to follow the recommended health protocols in the new normal policy. Keywords: Public Policy, New Normal, Compliance